2019
DOI: 10.1073/pnas.1808976116
|View full text |Cite
|
Sign up to set email alerts
|

The criminogenic and psychological effects of police stops on adolescent black and Latino boys

Abstract: Proactive policing, the strategic targeting of people or places to prevent crimes, is a well-studied tactic that is ubiquitous in modern law enforcement. A 2017 National Academies of Sciences report reviewed existing literature, entrenched in deterrence theory, and found evidence that proactive policing strategies can reduce crime. The existing literature, however, does not explore what the short and long-term effects of police contact are for young people who are subjected to high rates of contact with law en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
104
1
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(112 citation statements)
references
References 74 publications
2
104
1
5
Order By: Relevance
“…A low score represents fewer depressive symptoms, whereas a high score indicates the participant experienced more symptoms. The scale has been a reliable measure among a racially diverse sample of Black adolescent boys (α = 0.90; Del Toro et al 2019) and Black college students (α = 0.84; Norton 2007). It also demonstrated strong internal consistency in the current sample (α = 0.95).…”
Section: Depressive Symptomsmentioning
confidence: 66%
“…A low score represents fewer depressive symptoms, whereas a high score indicates the participant experienced more symptoms. The scale has been a reliable measure among a racially diverse sample of Black adolescent boys (α = 0.90; Del Toro et al 2019) and Black college students (α = 0.84; Norton 2007). It also demonstrated strong internal consistency in the current sample (α = 0.95).…”
Section: Depressive Symptomsmentioning
confidence: 66%
“…Violent policing contributes to community fragmentation (Gomez, 2016), and police killings have widespread adverse effects on Black adults in the impacted communities (Bor, Venkataramani, Williams, & Tsai, 2018). Proactive policing, in which particular areas or persons (often youth) are targeted with the intent of social control, can in some cases reduce immediate crime, but the research of Del Toro et al (2019), among others, confirmed serious immediate and long-term costs associated with police stops of young men of color, including more frequent criminal behavior up to 18 months later regardless of prior delinquency, as well as reduced psychological well-being.…”
Section: Race and Police Violencementioning
confidence: 99%
“…These effects may appear less “quantifiable” than hit rates or arrest rates, but they can in fact be measured, and they are essential to understanding how stop and frisk affects important criminal justice values such as engendering trust in law enforcement, providing motivation to conform to legal norms, and signaling the governmental commitment to equal treatment and due process. Moreover, there is evidence that aggressively policed communities become less safe, both because of the erosion of the bonds of trust between police and citizenry, and because repeated exposure to Terry stops may cause crime (Del Toro et al, in press; Tyler & Huo, ). Thus, the mismeasure of the intrusion is also a mismeasure of the efficacy of the police conduct, casting doubt on the basic rationale for stop and frisk.…”
Section: The Underexplored Part Of the Terry Equation: The Psychologimentioning
confidence: 99%
“…As Nikki Jones' () ethnographic study of adolescent and adult Black males in San Francisco's Fillmore neighborhood revealed, civilian–police interactions that are fraught with “abasements, degradations, humiliations and profanations of self” may radically shift one's “moral career” (p. 38). For example, through an analysis of longitudinal survey data from a sample of predominantly Black and Latino high school students, Del Toro et al (in press) found that adolescent boys who are stopped by police reported higher levels of lawbreaking behavior 6, 12, and up to 18 months after a police stop, independent of prior delinquency. They also found that psychological distress partially explains this relationship.…”
Section: The Underexplored Part Of the Terry Equation: The Psychologimentioning
confidence: 99%